Etiopathogenesis of Changes in the Hemodynamics of the Uterus and Placenta with Intrauterine Infection - Rakhimova Kamola Yuldashevna (Genius Journals, 2022)
Intrauterine infection of the fetus is an antenatal risk that causes fetal malformations and severe perinatal losses due to morphofunctional and hemodynamic disorders of the fetoplacental system.
Keywords: Fetoplacental insufficiency; intrauterine infection; hypoxia